2013
DOI: 10.1242/jcs.126813
|View full text |Cite
|
Sign up to set email alerts
|

The Munc18-1 domain 3a loop is essential for neuroexocytosis but not for syntaxin-1A transport to the plasma membrane

Abstract: SummaryMunc18-1 plays a dual role in transporting syntaxin-1A (Sx1a) to the plasma membrane and regulating SNARE-mediated membrane fusion. As impairment of either function leads to a common exocytic defect, assigning specific roles for various Munc18-1 domains has proved difficult. Structural analyses predict that a loop region in Munc18-1 domain 3a could catalyse the conversion of Sx1a from a 'closed', fusion-incompetent to an 'open', fusion-competent conformation. As this conversion occurs at the plasma memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 45 publications
5
67
0
Order By: Relevance
“…Fusion events were counted within the first 30 s of stimulation. Fusion events were detected as an increase in fluorescence intensity in TIR-illumination followed by the disappearance of a vesicle 31,32 (Fig. 5a).…”
Section: Svs and Cortical Actin Approach The Plasmalemma On Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusion events were counted within the first 30 s of stimulation. Fusion events were detected as an increase in fluorescence intensity in TIR-illumination followed by the disappearance of a vesicle 31,32 (Fig. 5a).…”
Section: Svs and Cortical Actin Approach The Plasmalemma On Stimulationmentioning
confidence: 99%
“…To examine whether the reduction in fusion events resulted from reduced SV docking in response to stimulation, we used PC12 cells engineered to knock down Munc18-1 and Munc18-2 (DKD-PC12 cells) 31 , which have been shown to exhibit defective vesicle docking 31,33 . Electron microscopy analysis revealed that the number of predocked granules in these cells was significantly reduced in comparison with that in DKD-PC12 cells in which wild-type Munc18-1 (Munc18-1) expression was rescued (Fig.…”
Section: Svs and Cortical Actin Approach The Plasmalemma On Stimulationmentioning
confidence: 99%
“…The cross-linking study has shown that the residues 333-339 of domain-3a (KMPQYQK) of Munc18-1 bind to the transmembrane proximal residues 87-91 (KYWWK) of synaptobrevin-2 (30). In addition, disrupting this region of the domain-3a of Munc18-1 by introducing deletion (Del 317-333) or insertion mutant (KE/5I) 3 caused severe secretion defects without impairing the chaperoning activity of Munc18-1 (11,12). Furthermore, the latter insertion mutant was found to interfere with the ability of Munc18-1 to bind to the preassembled SNARE complex (11).…”
mentioning
confidence: 99%
“…PC12 cells were routinely cultured as described previously (Osborne et al, 2008). Munc18 -1/2 double knock-down PC12 (DKD-PC12) cells were provided by Shuzo Sugita (University of Toronto, Toronto, Ontario, Canada) and maintained as described previously (Malintan et al, 2009;Martin et al, 2013). PC12 and DKD-PC12 cells were transfected using Lipofectamine LTX (Invitrogen) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…F-actin anchors SGs and provides tracks for their directed motion toward fusion sites (Giner et al, 2005). Molecular motors associated with F-actin, such as myosins (Malacombe et al, 2006), are involved in SG tethering (Tomatis et al, 2013), transport (Rose et al, 2002(Rose et al, , 2003, and the control of fusion kinetics and fusion pore size (Neco et al, 2004;Neco et al, 2008). The cortical actin network has also been shown to undergo large-scale reorganization, including partial depolymerization, in response to stimulation, not only in chromaffin cells (Aunis and Bader, 1988;Vitale et al, 1995) but also in adipocytes (Kanzaki and Pessin, 2001), pancreatic ␤-cells (Nevins and Thurmond, 2003), alveolar type II cells (Rose et al, 1999), and sea urchin eggs (Yonemura and Mabuchi, 1987).…”
Section: Introductionmentioning
confidence: 99%